Dataset of the transcribed 45S ribosomal RNA sequence of the tree crop yerba mate - Aguilera, Patricia Mabel (2017)
This contribution contains data related to the research article entitled The 18S-25S ribosomal RNA unit of yerba mate (Ilex paraguariensis A. St.-Hil.) (Aguilera et al., 2016). Through a bioinformatic approach involving NGS data, we provide information of the transcribed 45S ribosomal RNA (rRNA) sequence of yerba mate, the first reference for the Ilex L. genus. This dataset comprises information regarding the assembly and annotation of this rRNA unit. The generated data is applicable for comparative analysis and evolutionary studies among Ilex and related taxa. The raw sequencing data used here is available at DDBJ/EMBL/GenBank (NCBI Resource Coordinators, 2016) Sequence Read Archive (SRA) under the accession SRP043293 and the consensus 45S ribosomal RNA sequence has been deposited there under the accession GFHV00000000.